High sensitivity of nitrobenzene on the ZnO monolayer and the role of strain engineering - Martins, Nicolas F. [UNESP]; Laranjeira, José A. [UNESP]; Denis, Pablo A.; Sambrano, Julio R. [UNESP] (Elsevier, 2025)
Volatile organic compounds (VOCs) emissions have been a recurring problem that has challenged research centers to find new ways to monitor them. From this perspective, this work investigates nitrobenzene sensing through computational simulations, a well-known toxic compound, using the strained and strain-free two-dimensional (2D) ZnO monolayer, a traditional metal oxide semiconductor (MOS). The results indicate that nitrobenzene is adsorbed via strong physisorption on the 2D ZnO and maintains interaction with the sensor under thermal stimulus (500 K), as demonstrated via ab initio molecular dynamics (AIMD) simulations. The nitrobenzene also changes the ZnO band gap energy from 4.59 to 1.85 eV and shifts 0.35 eV the work function value. Under biaxial strain, the nitrobenzene becomes chemisorbed on the ZnO monolayer. Also, remarkable conductivity changes are observed with the nitrobenzene adsorption on the strained ZnO. Excellent values of sensitivity are found, 2.29 × 1023, 8.11 × 1022 and 2.80 × 1016 for strain-free ZnO and the maximum compressed and stretched ZnO monolayer, respectively. Short recovery times of 1.16 × 10−4 s (T = 300 K) and 6.89 × 10−8 s (T = 500 K) are also found for strain-free ZnO monolayer, indicating a great reusability for nitrobenzene. Consequently, the ZnO monolayer can be used to detect nitrobenzene.
Keywords: 2D materials; Gas sensor; Nitrobenzene; Strain engineering; ZnO